2002
DOI: 10.3758/bf03196324
|View full text |Cite
|
Sign up to set email alerts
|

Operant variability: Evidence, functions, and theory

Abstract: Although responses are sometimes easy to predict, at other times responding seems highly variable, unpredictable, or even random. The inability to predict is generally attributed to ignorance of controlling variables, but this article is a review of research showing that the highest levels of behavioral variability may result from identifiable reinforcers contingent on such variability. That is, variability is an operant. Discriminative stimuli and reinforcers control it, resulting in low or high variability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
217
0
47

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(281 citation statements)
references
References 154 publications
(230 reference statements)
14
217
0
47
Order By: Relevance
“…Perhaps a long interresponse time (i.e., lower rate) causes the rat to "cool off," producing longer and more variable bar presses. But Neuringer and his colleagues have shown that rewarding variation can cause it to increase (Neuringer, 2002). This could not explain the reward-probability effects observed here because the "variation" of a single bar press (how much it differed from recent bar presses, which is the sort of measure of variation that Neuringer has used) did not affect its probability of reward.…”
Section: Control Of Variationmentioning
confidence: 99%
See 3 more Smart Citations
“…Perhaps a long interresponse time (i.e., lower rate) causes the rat to "cool off," producing longer and more variable bar presses. But Neuringer and his colleagues have shown that rewarding variation can cause it to increase (Neuringer, 2002). This could not explain the reward-probability effects observed here because the "variation" of a single bar press (how much it differed from recent bar presses, which is the sort of measure of variation that Neuringer has used) did not affect its probability of reward.…”
Section: Control Of Variationmentioning
confidence: 99%
“…Many studies have found that variation increases during extinction (Balsam et al, 1998;Neuringer, 2002) …”
Section: Why Variation Increases During Extinctionmentioning
confidence: 99%
See 2 more Smart Citations
“…Barba cites Machado (1997), for example, whose studies showed that variation in response sequences can arise by differential reinforcement of switching between keys. Thus, the nominal criterion of lag n sequence differences by itself does not provide sufficient evidence of variability per se as a functional response class, never mind the putative role of an ''endogenous stochastic generator'' (Neuringer, 2002(Neuringer, , 2004. I'll say more about this concept later.…”
Section: Ri DXmentioning
confidence: 99%